Rule Based System Pemilihan Alternatif Merek Pembelian Notebook - dayat, nurhidayat; Antari, Primadela; Bufra, Fanny Septiani (Universitas Muhammadiyah Bangka Belitung, 2023)
With dozens of brands on the market, designed sustainably with the latest technology, making notebooks a complex product. Buyers use different notebook attributes in comparing alternative notebook brands with processor, memory system, screen, graphics, overall performance as determining attributes. Forward chaining is a strategy for drawing conclusions that starts from a number of known facts, to obtain a new fact by using rules that have premises that match the facts and continues until the goal is reached or until there are no rules that have suitable premises. or until you get the facts. Expert systems act as smart advisors or consultants by retrieving knowledge stored in a knowledge base. Even an inexperienced user, as long as they have a general understanding of how diagnostic equipment works, can solve complex problems and can make appropriate and accurate decisions like an expert would.